PENINGKATAN KETERAMPILAN MENULIS AKSARA JAWA MELALUI MODEL QUANTUM LEARNING DENGAN KARTU HURUF - Karniasari, Mujiyono, Fitria Dwi Prasetyaningtyas, Ika (Universitas Negeri Semarang, 2015)
Tujuan penelitian ini adalah meningkatkan keterampilan menulis aksara Jawa melalui model Quantum Learning dengan kartu huruf pada siswa kelas V SDN Bugangan 03 Semarang. Penelitian ini dilaksanakan 2 siklus, setiap siklus 2 pertemuan. Hasil penelitian menunjukkan; (1) keterampilan guru siklus I pertemuan 1 skor 28 (baik), siklus I pertemuan 2 skor 30 (baik), siklus II pertemuan I skor 35 (baik), siklus II pertemuan 2 skor 38 (sangat baik), (2) aktifitas siswa siklus I pertemuan 1 skor 22,5 (cukup), siklus I pertemuan 2 skor 22,7 (baik), siklus II pertemuan 1 skor 31,01 (baik), siklus II pertemuan 2 skor 33,61 (sangat baik), (3) keterampilan menulis aksara Jawa siklus I pertemuan 1 skor 5,65 (cukup), siklus I pertemuan 2 skor 6,38 (cukup), siklus II pertemuan 1 skor 8,5 (baik), siklus II pertemuan 2 skor 10,03 (sangat baik). Simpulan dalam penelitian ini adalah melalui model Quantum Learning dapat meningkatkan keterampilan menulis aksara Jawa.Ã‚Â The aim of this research is to improve the writing skill on Javanese alphabets through Quantum Learning with letter cards towards 5th graders at SDN Bugangan 03 Semarang. This investigation was done in two cycles consists of two meetings. The results of the study showed that (1) the teacher skill in the first cycle at the first meeting obtained the score of 28 (good) while at the second meeting gained the score of 30 (good) and in the second cycle gained the score 35 (good) while at the second meeting gained the score of 38 (very good) (2) students activities in the first cycle at the first meeting obtained the score of 22,5 (fair) while at the second meeting gained the score of 22,7 (good) and in the second cycle gained the score of 31,01 (good) while at the second meeting gained the score of 33,61 (very good) (3) the studentÃ¢â‚¬â„¢s writing skill on Javanese alphabets improved in the first cycle at the first meeting gained the score of 5,65 (fair) while at the second meeting gained the score of 6,38 (fair) and in the second cycle gained the score of 8,5 (good) while at the second meeting gained the score of 10,03 (very good). The study concluded that the Quantum Learning could improve the writing skill on Javanese alphabets.